Emblem, Bombay Port Trust - Ghosh, Ayan (2023)
Ballard Estate was named after John Archibald Ballard, founder of Bombay Port Trust (now Mumbai Port Trust), which was established as a corporation on 26 June 1873. The present-day docks were first built in the 1870s by the Bombay Port Trust and further expanded in phases on reclaimed land.